A Analisis Kolaborasi Perbankan Syariah dan Masjid Melalui Pendekatan Nudge Theory: Perspektif Jamaah Masjid di Kabupaten Purwakarta - Ade Wahyu Awaludin; Gusti Oka Widana (ITB AAS INDONESIA Surakarta, 2026)
This study aims to analyze the determinants of Islamic financial inclusion within mosque-based communities by integrating Islamic financial literacy, religiosity, nudge, and mosque–bank collaboration. A quantitative cross-sectional approach was employed using data from 120 respondents in Purwakarta Regency. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Islamic financial literacy has a positive and significant effect on Islamic financial inclusion and serves as the primary determinant in the model. Nudge also has a significant positive effect on inclusion, functioning as a complementary behavioral mechanism rather than a moderating variable. In contrast, religiosity does not have a significant direct effect on inclusion, indicating the presence of an attitude–behavior gap. Furthermore, religiosity negatively affects nudge, while collaboration does not significantly influence inclusion and shows a relatively small effect size. A notable finding is the negative moderating effect of mosque–bank collaboration on the relationship between religiosity and inclusion. This study contributes to the Islamic behavioral finance literature by highlighting the importance of integrating cognitive, behavioral, and institutional factors in promoting community-based Islamic financial inclusion.